Rural World as a Type of Legal Life of Society - A. A. Afanasyev (Сибирское юридическое обозрение, 2022)
The legal life of society as an object of legal knowledge can have various invariants (species, forms), which are complex self-developing systems with constantly changing quantitative and qualitative characteristics as they evolve (in time, space, and more). When they interact, there is a permanent change in the most integral object, which goes into more and more new phases. This type of integral object is the legal life of the rural world (rural life), covering the entire range of material and spiritual legal phenomena that arise when solving the tasks of state policy for the development of rural areas in order to improve the quality of life of the population, ensure national security and sovereignty of Russia. In this study, the subject of legal knowledge of the legal life of the village is formulated ideas, principles, legal relations (power, economic, environ-mental and other spheres of activity of the subjects), legal norms and other elements that collectively represent the foundations of the law of the rural world. The legal basis of rural life as a self-developing political and legal phenomenon is an effective tool for improving national positive law. The study of the foundations of the law of the rural world through a more detailed study of significant signs of its structural elements through the synthesis of methods, methods and processes of scientific knowledge allows you to objectively supplement the conceptual range of legal science.